Lymphocytic mastopathy: a great mimicry of carcinoma - Mahno, Noor Ezmas; ML, Nani Halina; AS, Sharun Niza; M, Rohaizak; AS., Nordashima (Surgical Society of Northern Greece, 2021)
Three elderly ladies presented with clinical suspicion of breast cancer. Lumpectomy was performed in all 3 cases and histopathological examination came back as lymphocytic mastopathy. Only one of them had a classical long history of diabetes to suggest diabetic mastopathy. The other two cases was non-diabetic and not associated with autoimmune disease. Clinicopathologic and imaging revisited. The disease posed a diagnostic challenges and management dilemma.